PRACTICAL TECHNOLOGIES OF OPTIMIZATION AND INTENSIFICATION OF COMMUNICATION DIDACTIC PROCESS - Булгакова, Н. Б.; Василишина, Н. М. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2015)
The article under consideration is devoted to the intensification and improvement of professional training process by means of implementing innovative technologies in educational process. In particular, the attention here is focused on theoretical and practical basis of the most effective communicative technology, namely training, and consideration of modernized technique